2018
DOI: 10.1007/s13659-018-0170-1
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Plant Using Ground State Stabilization of Natural Antioxidant Curcumin by Keto-Enol Tautomerisation

Abstract: Curcumin is a medicinal agent that exhibits anti-cancer properties and bioactive pigment in Turmeric has a huge therapeutic value. It has a keto-enol moiety that gives rise to many of its chemical properties. A recent study has shown that keto-enol tautomerisation at this moiety is implicated the effect of curcumin. The tautomerisation of curcumin in methanol, acetone and acetonitrile are used in nuclear magnetic resonance (1H, 13C) spectroscopy. It was characterized using UV, IR and Raman spectral values. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…In Figure 6 , we have collected representative UV-vis spectra for our thin-film samples from all the aforementioned sample categories. First of all, for the parent Cur, ZnO and TiO 2 films, the absorption maxima (λ max ) are seen—as expected—at 435 nm (due to the π − π* electronic transition of Cur [ 46 , 47 ]), at 360 nm [ 56 ], and at 422 nm, respectively. The slightly different λ max value of 435 nm for our Cur film as compared to the previous data for curcumin solutions (ca.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…In Figure 6 , we have collected representative UV-vis spectra for our thin-film samples from all the aforementioned sample categories. First of all, for the parent Cur, ZnO and TiO 2 films, the absorption maxima (λ max ) are seen—as expected—at 435 nm (due to the π − π* electronic transition of Cur [ 46 , 47 ]), at 360 nm [ 56 ], and at 422 nm, respectively. The slightly different λ max value of 435 nm for our Cur film as compared to the previous data for curcumin solutions (ca.…”
Section: Resultssupporting
confidence: 72%
“…The inset in Figure 2 a shows that this dependence of the film thickness on the Cur concentration in the solution is rather linear. The well-controlled S-C-growth of Cur films was further affirmed from the UV-vis absorption spectra ( Figure 2 b), showing the gradual (linear) increase of the absorption peak around 430 nm (originating from the π − π* electronic transition [ 46 , 47 ]) with increasing Cur concentration. From GIXRD (grazing-incidence X-ray diffraction) measurements, the films were found to be amorphous.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…As seen from Table S6, the standard thermodynamic functions increase with increasing temperature, due to the intensities of molecular vibration increase; it is observed that the entropy increases but the enthalpy and heat capacity remain constant. According to Boyle's law for gases, a molecule is compressed at constant temperature its volume decreases [17][18]. Due to decreasing volume, the number of possible sites that occupied by particles of the molecule may be restricted.…”
Section: Thermodynamic Propertiesmentioning
confidence: 99%
“…As shown in Figures 1a-b, there are two main forms of enol and keto for curcumin. It should be mentioned that the enol form is more energetically stable compared to the keto one (2,3). Moreover, this plant species has numerous chemical compounds including essential oils, alpha and beta turmeric, ginger, glucose, fructose, arabinose, and starch.…”
Section: Introductionmentioning
confidence: 99%